Prevalence of Stylopization of Sphex ichneumoneus (L.) (Hymenoptera: Sphecidae) by Paraxenos westwoodi (Templeton) (Strepsiptera: Xenidae) - Richard S. Miller; April M. Pearce; Kevin M. O'Neill (Psyche: A Journal of Entomology)
On a seed production farm in southcentral Montana, USA, we found the strepsipteran Paraxenos westwoodi (Templeton) parasitizing adult Sphex ichneumoneus (L.), which were collected while they were foraging for nectar. Over a two-year period, 25% of males and 7% of female wasps were stylopized, as evidenced by the presence of puparia and empty puparial cases of male and female P. westwoodi exserted dorsally between abdominal segments. Our estimate is based on a sample size larger than those usually reported for strepsipterans attacking solitary aculeate wasps. We review the literature on strepsipteran prevalence in solitary aculeate wasps and provide an updated list of solitary wasps known to act of strepsipteran hosts in North America.